Development of an integrated case-based digital accounting skills learning model to shape 21st century accountants - Marwan Marwan; Nelvirita Nelvirita; Rahmayuni Alfajri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study aims to develop and test the effectiveness of the Integrated Case-Based Digital Accounting Skills (ICDAS) learning model in equipping accounting students with 21st-century digital skills. This model was designed in response to the increasing industry demand for graduates with digital competencies, which until now has not been fully met by higher education. The study used a quasi-experimental design with a pretest-posttest approach in the experimental group (n=34) and the control group (n=34). The ICDAS model integrates case-based learning, the use of digital accounting tools, and artificial intelligence (AI), combined with the Joyce, Weil, and Calhoun approach and the Outcome-Based Education (OBE) principle. The results of expert validation showed a very high level of validity (4.60–4.70), and an excellent level of practicality (4.50–4.70). Empirically, this model has been proven effective in improving students' digital skills. The average posttest score of the experimental group (M=4.00) was significantly higher than the control group (M=3.45), with the t-test results showing significance (t(66)=5.86, p<0.001). The effect size analysis (Cohen's d = 1.77) showed a very large influence, while the N-Gain value (g = 0.41) was in the moderate category. In addition, the SEM-PLS analysis confirmed that the ICDAS model was a strong predictor of digital skills development (β = 0.72, p<0.001). These findings confirm that the ICDAS model is not only valid and practical, but also effective in improving the digital skills of accounting students.